Duration of stay in emergency department and outcomes of admitted patients - Acharya, Samita; Amatya, Yogendra (Journal of Patan Academy of Health Sciences, 2015)
Introductions: Duration of stay in Emergency Department (ED) is associated with negative outcomes, from increased mortality to increased duration of length of stay as inpatient. This study evaluates the length of duration of stay in ED after admission and the outcomes.Methods: This was a cross sectional observational study conducted at Patan Hospital, a tertiary care teaching hospital of Patan Academy of Health Sciences. All the patients presenting to ED and getting admitted from 21st July to 4th August 2014 were enrolled in the study. Primary outcomes were hospital mortality, length of hospital stays (days) and secondary outcome was rate of transfer of inpatient to ICU or step down for higher care.Results: There were total 178 admissions form ED during the study period. Length of hospital stay increased with the increased duration spent in ED (p=0.004). The mortality group also had increased duration of stay in ED with mean duration of 23.23 hours. Increased duration of stay in ED after admission was also directly related to increased inpatient higher care transfers and thus prolonged hospital length of stay.Conclusions: Increased duration of stay in ED after admission was associated with increased hospital stay, increased mortality and increased inpatient transfer for higher care.Journal of Patan Academy of Health Sciences, Vol. 2, No. 1, 2015. page: 7-11